2022
DOI: 10.1088/2631-8695/ac9115
|View full text |Cite
|
Sign up to set email alerts
|

EIT for tactile sensing: considering artefacts in hyperparameter selection

Abstract: Electrical impedance tomography (EIT) is employed in tactile sensing to create an image of impedance changes within a continuous sensor using electrodes placed only at the perimeter. Noise destabilizes EIT images, and the onset of instability is associated with the appearance of artefacts, which are spurious image features that are not associated with sensor responses to contacts. Artefacts are detrimental because the essential features of contacts, or targets, must be correctly represented, including how ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The mesh size used for the forward problem was the finest j2d4c, and for the inverse it was h2d4c. Prior work showed that results were mesh invariant [5]. The threshold f = 2 was used for the 1/f max amplitude set (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mesh size used for the forward problem was the finest j2d4c, and for the inverse it was h2d4c. Prior work showed that results were mesh invariant [5]. The threshold f = 2 was used for the 1/f max amplitude set (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The I-M patterns were next challenged by adding noise. A useful metric for evaluating the effects of noise on tactile sensing images is the onset of artefacts [5]. Susceptibility to noise was determined by finding the noise level at which artifacts just started to appear for a given λ.…”
Section: Noise Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, some reports have been evaluated using position error and resolution. 8,10,20) To evaluate more quantitatively, the following evaluation method was defined. The normalized size error (NSE) shown in Eq.…”
Section: ( ) =mentioning
confidence: 99%
“…6) Various optimization approaches for hyperparameters have been reported. [9][10][11][12][13] However, determining the optimal hyperparameter remains a challenging task.…”
mentioning
confidence: 99%